Investigation of the effect of silymarin on the liver in experimental sepsis - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2015)
The aim of the study is to investigate the possible protective effect of silymarin (extract of Silybum marianum) on the liver of septic rats was at early stage of sepsis. Polymicrobial sepsis was induced by the cecal ligation and perforation (CLP) technique. Sepsis and sepsis + silymarin treated groups received vehicle or silymarin (50 mg/kg, orally). The rats were decapitated 6 h after the CLP procedure. Protein, glutathione, lipid peroxidation levels, tissue factor activity and some enzyme activities were determined and polyacrylamid gel electrophoresis was carried on liver samples. TNF-a, IL-1b and IL-6 were determined in blood samples. Glutathione levels significantly increased and tissue factor activity significantly decreased in both sepsis and sepsis+silymarin treated groups when compared with control. Superoxide dismutase activity significantly decreased in sepsis+silymarin treated group when compared control and sepsis groups. No significant difference was found in electrophoresis protein bands. Blood proinflammatory cytokine levels were significantly decreased in silymarin treated sepsis group when compared with sepsis group. The effect of silymarin was not apparent since oxidative damage was not obvious in liver consequently it can be suggested that some protective mechanisms related with glutathione in liver may be involved in early stage sepsis.
Keywords: Sepsis; Silymarin; Liver; Tissue factor; Oxidative stress; TISSUE FACTOR; OXIDATIVE STRESS; INFLAMMATORY RESPONSES; REDUCED GLUTATHIONE; SILYBUM-MARIANUM; SEPTIC SHOCK; BABOON MODEL; ACUTE-PHASE; LATE-STAGE; ANTIOXIDANT